Energy Transition – China-Brazil Partnership to Provide Nature-Based Solutions - Danielle M.T. Denny; Olivia Bulla; J. Renato Peneluppi Jr (Ukrainian Policymaker)
Nature is our strongest ally in the fight against climate change and biodiversity loss. Intact ecosystems store carbon dioxide, secure food and water supplies and protect against natural disasters. Nature-based solutions (NBS) can create jobs and contribute to economic and social development. However, effective safeguards and standards are essential to achieve these benefits. Land degradation in Brazil alone, if successfully restored, can feed the world, providing fibre, biofuels, feed and also sequestering carbon. As countries face increasingly complex climate-related challenges that threaten sustainable development goals, NBS offers a cost-effective alternative to traditional grey infrastructure. They provide longterm resilience while delivering significant social and environmental benefits. Brazil and China have the opportunity to support biodiversity research to better understand the tipping points, trade-offs and underlying mechanisms of NBS and their successful implementation in terms of benefits to nature, human well-being and societal transformation, in order to lead the process of developing the technologies needed to achieve the Ecological Civilisation.